Poesia concreta na escola? Uma proposta para ensino-aprendizagem de literatura - Lima, José Luiz Andrade de (2021)
This work, entitled “The Concrete Poetry at School? A teaching-learning literature proposal”, aims to facilitate the reading / understanding, by students, of the process of identifying the constituent elements of concrete poetry in elementary school classrooms, Final Years. In this sense, a work will be proposed, to be developed with 8th grade students, from the John Kennedy State College, located in the Getúlio Vargas neighborhood, in Aracaju / SE, on concrete poetry and its characteristics, since this approach is not common at this teaching stage. This study is based on the research work developed by Campos (2006), Aguillar (2005), Grünewald (2002), Bosi (2017), Roiphe (2011-2012), Lajolo (1993), Cosson (2009), among others authors who support the study of concrete poetry, in addition to the guidelines provided in the National Common Curricular Base ─ BNCC ─ (BRAZIL, 2018) and the State of Sergipe Curriculum Framework (SERGIPE, 2018) for teaching / learning to read literary text in the classroom, in addition to research done on recent works published in ProfLetras, such as those by Batista (2017), Maciel (2019) and Silva (2019). The students will be introduced to concrete texts and, based on the text-author-reader relationship, proposed by Kock & Elias (2006), it is possible to verify the originality of this type of poem in the daily life of the 8th year student. The idea is for students to analyze how concrete poetry relates to their daily lives, in the most different functions and can, finally, identify characteristics that form concrete poetry, such as the process of verbal-visualization, the use of verbal and nonverbal language, poetic experimentalism, graphic, sound and semantic effects, geometric aspects, the suppression of verse and stanza, the disappearance of the lyrical self, the elimination of intimate poetry and rationalism, since their use greatly contributes to the understanding of various texts in order to facilitate the practice of the word-image relationship. Therefore, a Didactic Sequence was developed to seek a more effective learning in the process of reading concrete poems in which pioneering authors in this style will be presented to students so that their respective concrete poems can be identified, analyzed, understood and replicated.